EFFECT OF COATING ON THE PHYSICAL AND MORPHOLOGICAL QUALITY OF FRESH HEN EGG DURING STORAGE - Maulida Hayuningtyas; Christina Winarti; Sari Intan Kailaku; Hoerudin Hoerudin (Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian, 2021)
Hen egg is the most consumed animal food due to its high nutritional content, affordable and easy to obtain. However, eggs have the disadvantage for their short shelf life of about 7 days at room temperature. An effort to extend the shelf life of eggs including storing at low temperatures and/or coating. The research objective was to determine changes in the physical quality and morphology of chicken eggs coated with two material coating stored at room (25–29 °C) and AC/low (18–22 °C) temperature. The treatments tested were two kinds of coatings, namely gelatin and lime solution, and two storage temperature conditions, namely room and low temperature for 30 days. The study was conducted with three replications, each replication was observed on 5 eggs. The parameters observed were weight loss, Egg white index, Egg yolk index, air cavity, Haugh Unit and surface morphology. The results showed that at the end of storage for 30 days the eggs quality still met the SNI standards I to III. AC storage temperature was better than room temperature. The egg treated with coating produced better quality than without coating. The longer the storage, the lower the weight loss, HU, IPT and IKT. The best treatment was gelatin coating stored at AC temperature.